2022
DOI: 10.3390/fermentation8070327
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Toxic Biogenic Amines in Various Types of Soft and Hard Cheeses and Their Control by Bacillus polymyxa D05-1

Abstract: Egyptian cheeses are considered an important part of the Egyptian diet. This study aimed to examine 60 random samples of different types of commercial cheeses in Egypt, including soft cheeses (Domiati and Tallaga) and hard cheeses (Cheddar and Ras). The samples were subjected to chemical and microbial examination. Biogenic amines (BAs) are nitrogenous compounds found in a variety of foods; their presence is undesirable and related to spoilage, and can result in toxicological effects in humans. Thus, BAs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…. E ect of chitosan-bioactive coatings on biogenic amine formation Because BAs are an important tool for evaluating the sanitary condition of foods, they can be utilized as indicators of food spoilage and, at high concentrations, can have toxicological consequences on consumers (Saad et al, 2022). Biogenic amine formation depends mainly on the decarboxylase enzyme that is secreted by spoilage or pathogenic bacteria (Xia et al, 2016;Kuley et al, 2019;Burgut, 2020).…”
Section: Statistical Analysismentioning
confidence: 99%
“…. E ect of chitosan-bioactive coatings on biogenic amine formation Because BAs are an important tool for evaluating the sanitary condition of foods, they can be utilized as indicators of food spoilage and, at high concentrations, can have toxicological consequences on consumers (Saad et al, 2022). Biogenic amine formation depends mainly on the decarboxylase enzyme that is secreted by spoilage or pathogenic bacteria (Xia et al, 2016;Kuley et al, 2019;Burgut, 2020).…”
Section: Statistical Analysismentioning
confidence: 99%
“…As for the other samples, the TYR concentrations ranged from 0.52 to 2.19 mg/kg. Crucially, none of the TYR levels in the samples examined exceeded the suggested limit of 100 mg/kg . It is important to note that some samples, such as Egyptian herring, exceeded the 50 ppm histamine limits set by the FDA.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [37] also observed a 74% histamine degradation in the B. subtilis broth within 24 h, and Paenibacillus polymyxa exhibited 100% degradation of histamine. Bacillus strains that are able to degrade biogenic amines have also been isolated from other foods, such as various types of cheese [38], shuidouchi [39], or from fish sauce [40].…”
Section: Resultsmentioning
confidence: 99%